Lipschitz Continuity and Explicit Form of Solution in a Class of Free Boundary Problem with Neumann Boundary Condition (Journal of Partial Differential Equations, 2023)
We consider a class of free boundary problems with Neumann boundaryconditions. We would like to give certain results with regularity of solutions (mainlythe local interior and boundary Lipschitz continuity). We will also show an explicitform of solution under well-specified conditions.